Hubungan Dukungan Orang Tua Terhadap Motivasi Belajar Siswa Kelas IV di SD N 2 Ketol - Zahara, Nita; Marnola, Ilham; Dhari, Putri Wulan (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
This study aims to determine the relationship between parental support and learning motivation of fourth grade students at SDN 2 Ketol. The background of this study is based on the importance of parental participation in the support or learning process of children, especially in shaping children's positive attitudes and enthusiasm for learning. The method used in this study is a quantitative method with a correlational approach. Data collection techniques were carried out through questionnaires distributed to fourth grade students as well as documentation and supporting interviews. The results showed that there is a significant relationship between parental support and student learning motivation. This finding shows that the active involvement of parents in children's education is very important in increasing children's motivation and learning achievement in elementary school.Hypothesis testing is the final stage in this study. The test was carried out using the F test, which aims to determine whether there is an influence of the independent variable (X) on the dependent variable (Y). If the value obtained is more than 0.40, it can be concluded that there is a relationship between variable X and variable Y. Conversely, if the value is less than 0.40, then there is no relationship between the two variables.